2022
DOI: 10.3389/fonc.2022.916804
|View full text |Cite
|
Sign up to set email alerts
|

The Isoforms of Estrogen Receptor Alpha and Beta in Thyroid Cancer

Abstract: The incidence of thyroid cancer was predominant in women, indicating that the sex hormone may have a role in thyroid cancer development. Generally, the sex hormone exerts its function by binding to the correspondent nuclear receptors. Therefore, aberrant of these receptors may be involved in the development of thyroid cancer. Estrogen receptor alpha (ERα) and beta (ERβ), two main estrogen receptors, have been reported to have an important role in the pathogenesis of thyroid cancer. When the ERα and ERβ genes u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Thyroid cancers are prevalent in women, indicating the sex hormone disorders as an essential risk factor [ 84 ]. The peroxisome proliferator receptor gamma (PPARγ) alteration associated with steroids transcriptional factors was detected only in follicular thyroid cancer and follicular adenoma [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid cancers are prevalent in women, indicating the sex hormone disorders as an essential risk factor [ 84 ]. The peroxisome proliferator receptor gamma (PPARγ) alteration associated with steroids transcriptional factors was detected only in follicular thyroid cancer and follicular adenoma [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…The association of hsa-mir-125b with STAT3, PRDM1, TP53, EZH2, NFkB1, AKT1, ERS1 and PPARG was revealed. The complex of factors represented the processes activated in PTC development [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 ]. They recover the mechanism of immune response, microenvironment modification, hormone receptors signal transduction, oxidative stress and etc.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the development of TC is closely related to estrogen levels in the human body[ 24 , 25 ]. It has been reported that TSH is one of the main regulatory hormones that regulate thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we will primarily focus on the identified functional diversity of ERα variants in physiological conditions. For the reviews on an extensive list of ERα variants in cancer, we refer the readers to previous excellent reviews [ 1 , 2 , 3 , 4 ].…”
Section: Estrogen Receptor Alpha (Erα)mentioning
confidence: 99%